Adaptive interpretation of gas well deliverability tests with generating data of the IPR curve; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Sergeev V. L. Viktor Leonidovich (2017, 2017)
Title screen